2023
DOI: 10.3390/healthcare11040577
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Liability and Thyroidectomy: When Is the Surgeon Wrong?

Abstract: Thyroid surgeries can often lead to operative complications, sometimes with consequences on the patient’s health. This often leads to claims for compensation but the assessments of consultants and judges are not always objective. Based on these considerations, the authors analyzed forty-seven sentences issued between 2013 and 2022 regarding claims of alleged medical malpractice. This analysis aims to examine the cases presented in the sentences and the evaluations proposed by the judges to offer ideas for obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…An Italian study has identified over the last ten years 50 lawsuits related to thyroid surgery, mainly related to recurrent laryngeal nerve palsies, and three-quarters of these resulted in a conviction with financial damage awards. The decisions to grant the claims were all motivated on the basis of deficiencies in the plaintiffs’ medical records, particularly with regard to the descriptions of the surgical procedures performed ( 5 ). In England, between 1995 and 2012, there were a total of 161 claims, the majority of which related to lack of preoperative information, misdiagnosis and laryngeal recurrent nerve palsies ( 6 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An Italian study has identified over the last ten years 50 lawsuits related to thyroid surgery, mainly related to recurrent laryngeal nerve palsies, and three-quarters of these resulted in a conviction with financial damage awards. The decisions to grant the claims were all motivated on the basis of deficiencies in the plaintiffs’ medical records, particularly with regard to the descriptions of the surgical procedures performed ( 5 ). In England, between 1995 and 2012, there were a total of 161 claims, the majority of which related to lack of preoperative information, misdiagnosis and laryngeal recurrent nerve palsies ( 6 ).…”
mentioning
confidence: 99%
“…The claim for compensation was not upheld since the surgeons, under the conditions in which they were operating, could not prevent what in fact happened. In Italy, under Article 2236 of the Civil Code, “If the service involves the solution of technical problems of special difficulty, the service provider is not liable for damages, except in cases of malice or gross negligence” ( 5 ). In France, following a recurrent bilateral laryngeal nerve palsy after thyroidectomy which required a tracheostomy, liability was not attributed to the medical professionals by the Administrative Court because the complication was too rare to be predicted but encouraged the payment by the national health insurance of an indemnity in view of the functional damage presented by the patient (Administrative Court of Appeal of Bordeaux 2nd chamber, October 17, 2017).…”
mentioning
confidence: 99%